Moisture permeable sheet, total heat exchange element and total heat exchanger using the same, and air conditioning system
By using a breathable metal composite material containing multimetal composite and water repelent agent in the total heat exchanger separation plate, the problem of degradation of equipment performance in the prior art in high humidity environments is solved, and the combination of high humidity and water resistance is achieved, and the service life of the equipment is extended.
Patent Information
- Application Number
- JP2021008984
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-01-22
AI Technical Summary
The existing total heat exchanger separation plates have problems such as water droplet condensation, freezing and molds in high humidity environments, resulting in degradation of equipment performance and shortening of service life. At the same time, the existing technology is difficult to achieve both high water resistance, high heat conduction and high humidity.
Breathable metal composites containing polymetal composites and water repelent agents are used as separation plate materials, which have significant water resistance and water repelency properties under low humidity and high humidity conditions while maintaining high moisture permeability.
It achieves high humidity and water resistance in high humidity environments, extends the service life of the equipment, and improves the performance and stability of the total heat exchanger.
Smart Images

Figure 0007661705000004 
Figure 0007661705000005 
Figure 0007661705000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a total heat exchange element and a total heat exchanger for exchanging heat between air currents, which are used mainly in the field of air conditioning, and a moisture permeable sheet used therein. [Background technology]
[0002] In recent years, the importance of ventilation has increased due to the expansion of residential areas equipped with air conditioning systems such as heating and cooling, and the improvement of airtightness and insulation of houses. Total heat exchangers, which can recover temperature and humidity in this ventilation, are becoming increasingly important as air conditioning equipment that balances indoor air quality and energy conservation. Such total heat exchangers exchange temperature and humidity between two types of fluids using a partition plate that has thermal conductivity and moisture permeability, and are configured as multiple layers stacked at specified intervals with a partition plate sandwiched between them.
[0003] The performance required for the partitions of a total heat exchanger is low air permeability (high air barrier properties) and high heat transfer and moisture permeability. This is to enable efficient heat exchange of sensible heat and latent heat at the same time, without mixing the fresh outside air drawn in from the outdoors and the polluted inside air containing a lot of carbon dioxide exhausted from the inside to the outdoors during use.
[0004] On the other hand, existing total heat exchange elements do not have sufficient water repellency or water resistance, and therefore, for example, when used in cold regions, the inside of the total heat exchanger that has frozen in winter condenses in early spring, causing problems such as the total heat exchange element deforming or deteriorating due to condensation water, or the useful life being significantly shortened due to mold, etc. In some regions, heat exchange elements are washed with water, and there are very few total heat exchange elements that can withstand washing, which has slowed their spread.
[0005] In order to maintain long-term stability without change even in an environment where condensation occurs repeatedly, for example, Patent Document 1 discloses a composite moisture-permeable membrane as a partition plate for a total heat exchanger, in which a water-insoluble hydrophilic polymer thin film that allows water vapor to pass through is formed on one side of a porous sheet. Patent Document 2 discloses a gas barrier membrane as a partition plate for a total heat exchanger, in which a thin film having gas barrier properties is polymerized on a porous material.
[0006] Furthermore, Patent Document 3 discloses a sheet as a partition plate for a total heat exchanger, which comprises a porous member containing organic fibers and a membrane containing inorganic fibers having an average fiber diameter of 1 nm or more and 50 nm or less and which is provided on one side of the porous member, and which achieves both high moisture permeability and water repellency. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 2639303 [Patent Document 2] Patent No. 2738284 [Patent Document 3] JP 2020-038024 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, when a moisture-permeable, water-insoluble hydrophilic thin film is formed on one side of a porous substrate as in Patent Documents 1 and 2, moisture permeability is sacrificed in order to provide water repellency and water resistance, making it difficult to obtain a satisfactory moisture exchange efficiency. In addition, the moisture-permeable sheets as in Patent Documents 1 to 3 have a multi-layer structure and a complex configuration, which poses problems in terms of cost, moldability, and ease of assembly.
[0009] The present invention has been made to solve the problems of the conventional technology described above, and its object is to provide a moisture-permeable sheet that combines high water resistance and water repellency with high moisture permeability and does not have a complicated structure, and a total heat exchange element and a total heat exchanger that use said sheet, as well as an air conditioning system. [Means for solving the problem]
[0010] As a result of intensive research into achieving the above-mentioned object, the inventors have discovered that by incorporating a water repellent and a porous metal complex that has a high difference in saturated moisture adsorption rate between the low humidity side (30-40% RH) and the high humidity side (60-70% RH), it is possible to impart water resistance and water repellency while maintaining high moisture permeability with a simple structure, and have completed the present invention.
[0011] That is, the present invention comprises the following: The moisture-permeable sheet of the present invention is a moisture-permeable sheet used in a total heat exchange element that exchanges sensible heat and / or latent heat between two air streams, and contains a porous metal complex having a metal and an organic ligand, and a water repellent agent, and is characterized in that the difference in saturated moisture adsorption rate between 25°C and a relative pressure of 0.6 and 25°C and a relative pressure of 0.3 is 20 mass% or more.
[0012] Here, the pressure at which the adsorption process appears to have stopped under a constant pressure (number of adsorbed molecules = number of desorbed molecules) is called the adsorption equilibrium pressure, and the ratio of the adsorption equilibrium pressure to the saturated vapor pressure is called the relative pressure.
[0013] The moisture permeable sheet of the present invention preferably contains non-fibrillated fibers and fibrillated fibers, and further preferably contains an organic binder having a water dissolution temperature of 65°C to 100°C.
[0014] In the moisture permeable sheet of the present invention, the central metal of the porous metal complex is preferably a metal ion other than Pb, Hg, As, Cd, Cr, or Ni. Furthermore, in the moisture permeable sheet of the present invention, the porous metal complex preferably contains an iron ion and trimesic acid, a titanium ion and terephthalic acid, or a zirconium ion and terephthalic acid.
[0015] The moisture permeable sheet of the present invention preferably contains 40% by mass or more of the porous metal complex.
[0016] In the moisture permeable sheet of the present invention, the water repellent preferably contains a structure derived from styrene and acrylic.
[0017] Furthermore, in the moisture permeable sheet of the present invention, the water repellent agent preferably has an alkyl chain represented by the following chemical formula: [ka]
[0018] The moisture permeable sheet of the present invention is preferably configured so as to contain the water repellent agent in an amount of 2% by mass to 10% by mass.
[0019] The total heat exchange element of the present invention is characterized by comprising any one of the moisture permeable sheets of the present invention as a partition plate, two air flows having different temperatures and / or humidities are circulated across the partition plate, and sensible heat and / or latent heat of the two air flows are exchanged through the partition plate. The total heat exchanger of the present invention is characterized by comprising the total heat exchange element of the present invention. The air conditioning system of the present invention is characterized by comprising the total heat exchanger of the present invention and a heat pump. Alternatively, the air conditioning system of the present invention is characterized by comprising the total heat exchanger of the present invention and a desiccant air conditioner. Effect of the Invention
[0020] According to the present invention, it is possible to provide a moisture permeable sheet having a simple structure that achieves both moisture permeability and water resistance and water repellency at a higher level than conventional ones, and that does not have a complicated structure. Therefore, it is possible to provide a total heat exchange element, a total heat exchanger, and an air conditioning system that have high moisture exchange performance, safety, and stability in a high humidity environment or a condensation environment, and are easy to wash with water. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic diagram of a total heat exchanger according to an embodiment of the present invention. [Diagram 2] 1A is a perspective view of a total heat exchange element, and FIG. 1B is a front view of one layer of the total heat exchange element. [Diagram 3] 1A is a perspective view of a partition plate, FIG. 1B is a perspective view of a spacer plate, and FIG. 1C is a perspective view of one layer in which partition plates and spacers are stacked together. [Figure 4] FIG. 11 is a schematic diagram showing the configuration of a modified example of a total heat exchanger of the present invention. [Diagram 5] FIG. 11 is a schematic diagram showing the configuration of a total heat exchanger according to another modified example of the present invention. [Figure 6] FIG. 1 is a diagram showing an example of an air conditioning system equipped with a total heat exchanger and a heat pump according to the present invention. [Figure 7] FIG. 1 is a diagram showing an example of an air conditioning system equipped with a total heat exchanger and a desiccant air conditioner according to the present invention. [Figure 8] FIG. 1 is a diagram showing an example of an air conditioning system equipped with a total heat exchanger of the present invention, a desiccant air conditioner, and a heat pump. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. In the drawings, the same components are designated by the same reference numerals and the description will not be repeated.
[0023] 1 shows a schematic configuration of a total heat exchanger 1 of this embodiment. The total heat exchanger 1 is a device equipped with a total heat exchange element 2 that exchanges sensible heat and / or latent heat (sensible heat and latent heat in this embodiment) between two air flows (air flows in this embodiment). The total heat exchanger 1 contributes to energy saving by reducing the power consumption load of an air conditioner that adjusts temperature and humidity when comfortable air is supplied by the air conditioner to spaces in various facilities such as houses, buildings, condominiums, hospitals, factories, and stores, and spaces in various vehicles that transport people and cargo such as automobiles, trains, and airplanes.
[0024] In Fig. 1, OA indicates air (outdoor air) drawn into the total heat exchanger 1 from outdoors, SA indicates air sent from the total heat exchanger 1 to the inside or room, RA indicates air (indoor air) drawn into the total heat exchanger 1 from the inside or room, and EA indicates air (exhaust air) sent from the total heat exchanger 1 to the outdoors. In this embodiment, the air to be treated that is subjected to total heat exchange is outdoor air, but the air to be treated is not limited to outdoor air. In addition, for the purpose of purifying the air or protecting the total heat exchange element 2, it is preferable to install a prefilter having the ability to remove coarse particles, bacteria, or viruses at the intake port or the like.
[0025] In this embodiment, the total heat exchanger 1 is a stationary type total heat exchanger, and includes a housing 4 provided with air intakes 50, 51 and exhausts 60, 61, and a total heat exchange element 2 arranged in the housing 4. The total heat exchange element 2 is an element that exchanges sensible heat and / or latent heat between two air flows with different temperatures and humidities. A frame 40 that fixes the total heat exchange element 2 and a partition wall 41 that prevents the air flows from mixing inside the housing 4 are provided inside the housing 4.
[0026] 2A is a perspective view of the total heat exchange element 2, and FIG. 3B is a cross-sectional view of a portion of the total heat exchange element 2. FIGS. 3A to 3C are diagrams showing the partition plates 3A and the spacing plates 3B constituting the total heat exchange element 2. As shown in FIGS. 2 and 3, the total heat exchange element 2 has a laminate structure in which a single-layered sheet 3C composed of the partition plates 3A and the spacing plates 3B formed of the moisture-permeable sheet 3 is laminated in a plurality of layers, as described later, and is installed in a housing 4 so that air flows in a direction perpendicular to the stacking direction. In this embodiment, the partition plates 3A and the spacing plates 3B constituting the total heat exchange element 2 are formed of the moisture-permeable sheet 3, but it is sufficient that at least one of them is formed of the moisture-permeable sheet 3.
[0027] 1 and 2, two types of airflows can pass through the inside of the total heat exchange element 2 in a cross flow manner, the first airflow passing through the inside of the total heat exchange element 2 only from the openings 21 of the total heat exchange element 2 in a direction perpendicular to the lamination direction from one end face of the total heat exchange element 2 to the other end face, and the second airflow passing through the inside of the total heat exchange element 2 only from the openings 23 of the total heat exchange element 2 in a direction perpendicular to the lamination direction from one end face of the total heat exchange element 2 to the other end of the adjacent left and right faces of the total heat exchange element 2 relative to the first airflow. The moisture permeable sheet 3 constituting the total heat exchange element 2 carries a moisture absorbent capable of adsorbing moisture (water vapor) in the airflow passing through the inside of the total heat exchange element 2.
[0028] Here, the moisture absorbent supported on the moisture permeable sheet 3 is not an inorganic porous material such as silica gel, zeolite, or activated carbon that is generally used in conventional total heat exchange elements and total heat exchangers, but a porous material that is self-assembled by combining metal ions that can take various coordination forms with organic ligands having two or more coordination sites, that is, a porous material called a porous metal oxide framework (MOF) or a porous coordination polymer (PCP). A framework structure is constructed by bridging the metal ions that serve as nodes with organic ligands, and the voids in this framework act as spaces that capture moisture. A porous metal complex (or a porous coordination polymer) is usually synthesized by a reaction in a solution. That is, a crystalline compound is obtained by dissolving a metal ion source and a compound having an organic ligand in a solvent such as water or an organic solvent and heating it. Immediately after synthesis, the solvent molecules are included inside the lattice of the framework, but by removing these solvent molecules, the porous material is obtained.
[0029] Porous metal complexes have a high specific surface area compared to inorganic porous materials such as silica gel, zeolite, and activated carbon, and therefore have the advantage that they have a large adsorption capacity for moisture in the air, and when used as a moisture permeable sheet, they can increase the effective contact area with water molecules.In addition, because they have a sharp pore distribution, they have an isotherm shape in which the amount of adsorbent adsorbed rises sharply at a certain relative pressure (threshold relative pressure), and therefore the difference in saturated adsorption amount before and after the threshold relative pressure becomes large, and they have the advantage that when used as a moisture permeable sheet, the amount of moisture permeated becomes large.
[0030] As the metal constituting the porous metal complex, it is preferable to use metals classified into Groups 2, 4, and 7 to 14 of the periodic table. Among them, Group 2 elements such as Mg, Ca, and Ba; Group 4 elements such as Ti and Zr; Group 7 elements such as Re; Group 8 elements such as Fe; Group 9 elements such as Rh and Ir; Group 10 elements such as Pd and Pt; Group 11 elements such as Cu, Ag, and Au; Group 12 elements such as Zn; Group 13 elements such as Al; and Group 14 elements such as B and Si are preferable, and Group 4 and Group 7 to Group 14 elements are more preferable, and among them, the use of Ti, Zr, Fe, Cu, Zn, Al, and Si is optimal for the present invention. For example, dicarboxylic acids and derivatives thereof such as terephthalic acid, isophthalic acid, 2,5-dihydroxyterephthalic acid, 1,4-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 3,3'-biphenyldicarboxylic acid, fumaric acid, malonic acid, and adipic acid; tricarboxylic acids and derivatives thereof such as biphenyl-3,4',5-tricarboxylic acid, 1,3,5-tris(4'-carboxy[1,1'-biphenyl]-4-yl)benzene, 1,3,5-tris(4-carboxyphenyl)benzene, and 1,3,5-benzenetricarboxylic acid; tetracarboxylic acids such as p-terphenyl-3,3',5,5'-tetracarboxylic acid (also known as 5,5'-(1,4-phenylene)bisisophthalic acid) and 1,2,4,5-tetrakis(4-carboxyphenyl)benzene. acids and derivatives thereof; imidazoles and derivatives thereof, such as imidazole, 2-methylimidazole, and 2-phenylimidazole; pyrazoles and derivatives thereof, such as 4,4'-bipyrazolate, 3,3',5,5'-tetramethyl-4,4'-bipyrazolate, and 1,3,5-tris(1H-1,2-pyrazol-4-yl)benzene; triazoles and derivatives thereof, such as 1,3,5-tris(1H-1,2,3-triazol-5-yl)benzene; tetrazoles and derivatives thereof, such as 5,5'-bistetrazole, 5,5'-azobis-1H-tetrazole, and 1,3,5-tris(2H-tetrazol-5-yl)benzene; pyridines and derivatives thereof, such as 1,2-bis(4-pyridyl)ethane and 4,4'-bipyridine; triethylenediamine, pyrazine, piperazine, and the like. Of these, terephthalic acid and trimesic acid are preferably used in the present invention.
[0031] Specific examples of the porous metal complex include, but are not limited to, porous metal complexes composed of aluminum ions and terephthalic acid (e.g., Basolite A100 manufactured by BASF), porous metal complexes composed of iron ions and trimesic acid (e.g., Basolite F300 manufactured by BASF), porous metal complexes composed of titanium ions and terephthalic acid, and porous metal complexes composed of zirconium ions and terephthalic acid. These porous metal complexes have various BET specific surface areas depending on the synthesis method and purity, even if they are the same porous metal complex. Among these porous metal complexes, it is preferable to use porous metal complexes composed of iron ions and trimesic acid, titanium ions and terephthalic acid, and zirconium ions and terephthalic acid, because they use metals with low toxicity to take environmental pollution into consideration and have sites that can be moderately bonded to water.
[0032] In this embodiment, the porous metal complex is characterized in that the difference in saturated moisture adsorption rate between 25°C and a relative pressure of 0.6 and 25°C and a relative pressure of 0.3 (hereinafter, simply referred to as "saturated moisture adsorption rate difference") is 20% by mass or more. If the difference in saturated moisture adsorption rate between low humidity (relative pressure 0.3) and high humidity (relative pressure 0.6) is large, the driving force of moisture movement when made into a moisture permeable sheet tends to be high, and the humidity exchange rate after being made into an element tends to be high. If the difference in saturated moisture adsorption rate between 25°C and a relative pressure of 0.6 and 25°C and a relative pressure of 0.3 of the porous metal complex is 20% by mass or more, the moisture permeable sheet 3 has excellent moisture permeability and enables highly efficient humidity exchange. The above-mentioned difference in saturated moisture adsorption rate of the porous metal complex is not particularly limited as long as it is 20% by mass or more, but it is more preferably 25% by mass or more, and even more preferably 30% by mass or more.
[0033] In addition, the porous metal complex preferably has a saturated moisture adsorption rate of 30% by mass or more at 25° C. and a relative pressure of 0.6, more preferably 35% by mass or more, and even more preferably 40% by mass or more. Since the saturated moisture adsorption rate of the porous metal complex at 25° C. and a relative pressure of 0.6 is 30% by mass or more, the saturated moisture adsorption rate difference is increased, and the moisture permeable sheet 3 itself carrying the porous metal complex can retain a large amount of moisture, so that the moisture permeable sheet 3 can be given flexibility. This allows the content of the organic binder described below, which is involved in giving flexibility to the moisture permeable sheet 3, to be reduced. Therefore, it is possible to suppress the decrease in the adsorption performance of the porous metal complex caused by the side chains of the organic binder being adsorbed into the pores of the porous metal complex and blocking the pores. In addition, since the moisture permeable sheet 3 has good flexibility, the moisture permeable sheet 3 can easily be subjected to step processing such as the spacing plate 3B subjected to corrugation processing described below. Furthermore, the total heat exchange element 2 formed by the moisture permeable sheet 3 also has flexibility, which improves stability and durability for long-term use.
[0034] The saturated water adsorption rate [%] of a porous metal complex at 25°C and a relative pressure of 0.5 can be calculated from the water adsorption amount [g] per 1 g of porous metal complex at a relative pressure of 0.5 using the following formula 1, as described in detail later in the Examples.
[0035] Saturated moisture adsorption rate [%] = amount of moisture adsorbed per 1 g of moisture absorbent [g] × 100 (Equation 1)
[0036] Similarly, the saturated moisture adsorption rate of the porous metal complex at 25°C and a relative pressure of 0.3 is calculated using the above formula 1, and the saturated moisture adsorption rate difference can be calculated by subtracting the saturated moisture adsorption rate of the porous metal complex at 25°C and a relative pressure of 0.3 from the saturated moisture adsorption rate of the porous metal complex at 25°C and a relative pressure of 0.6.
[0037] The form of the porous metal complex is not particularly limited, and may be, for example, a powder or granule. The average particle size of the porous metal complex is not particularly limited, but is preferably 0.1 μm to 200 μm, more preferably 1 μm to 100 μm, and even more preferably 1 μm to 80 μm. By having the average particle size of the porous metal complex be 0.1 μm or more, a decrease in yield during the production of the moisture-permeable sheet 3 carrying the porous metal complex can be suppressed, while by having the average particle size be 200 μm or less, the porous metal complex can be favorably carried on the moisture-permeable sheet 3, and thus the falling off of the porous metal complex from the moisture-permeable sheet 3 can be suppressed. The average particle size of the porous metal complex can be measured, for example, using a scanning electron microscope.
[0038] The BET specific surface area of the porous metal complex measured by the 77K nitrogen adsorption method is not particularly limited, but is preferably 900 m 2 / g or more, and 1500m 2 / g or more is more preferable, and 1800m 2 It is more preferable that the BET specific surface area of the porous metal complex is 900 m 2 / g or more, the porous metal complex can effectively exhibit its superior adsorption performance to inorganic porous materials. The upper limit of the BET specific surface area of the porous metal complex is not particularly limited, but is preferably 6000 m 2 / g or less. The BET specific surface area is preferably 6000 m 2 / g or less, a porous metal complex can be easily produced.
[0039] Here, the BET specific surface area of the porous metal complex is measured by taking about 100 mg of the porous metal complex (before treatment with water or an organic solvent), vacuum drying it at 120°C for 12 hours, weighing it, and then using an automatic specific surface area measuring device (Gemini 2375, manufactured by Micromeritics), measuring the amount of adsorption of nitrogen gas at the boiling point of liquid nitrogen (-195.8°C) at 40 points while gradually increasing the relative pressure in the range of 0.02 to 0.95, and creating an adsorption isotherm. Then, using the analysis software (GEMINI-PCW version 1.01) attached to the automatic specific surface area measuring device, the BET specific surface area (m 2 / g) can be calculated.
[0040] The moisture absorbent may contain one or more kinds of porous metal complexes. Furthermore, as long as the moisture absorbent contains a porous metal complex as a main component, it may contain a porous material other than the porous metal complex, for example, an organic polymer porous material such as activated carbon, zeolite, silica gel, activated alumina, aluminophosphate, silicoaluminophosphate, or styrene-divinylbenzene copolymer. The main component means that the proportion of the main component to the entire moisture absorbent is 20% by mass or more, preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 80% by mass or more.
[0041] As shown in Fig. 2(A), the total heat exchange element 2 is configured such that open layers 21, 23 through which airflow can pass and closed layers 22, 24 through which airflow cannot pass are alternately laminated, and two airflows pass perpendicularly to the lamination direction. The open layers 21, 23 and closed layers 22, 24 are formed from a single-step sheet 3C described later. The open layer 21 through which one airflow passes is a closed layer 24 on the other airflow side, and similarly, the open layer 23 through which the other airflow passes is a closed layer 22 on the one airflow side. This configuration allows the two types of airflow to pass through the total heat exchange element 2 without mixing.
[0042] As shown in FIG. 2(B), the total heat exchange element 2 has a honeycomb structure in which a plurality of spaces 20, which are partitioned from one another, are arranged along a plane. The plurality of spaces 20 are arranged regularly or irregularly in a plane in a vertical, horizontal, diagonal, or other direction, and are perforated so that air flow can pass through. In other words, the spaces 20 are air flow paths. The spaces 20 are alternately perforated in a direction perpendicular to the stacking direction for each layer of the single-column sheet 3C described later in the total heat exchange element 2. The cross-sectional shape of the space 20 on the air flow passage surface is not particularly limited, and in the illustrated embodiment, the cross section is triangular, but may also be, for example, rectangular, rhombic, hexagonal, or circular.
[0043] The total heat exchange element 2 is formed by a moisture-permeable sheet 3 carrying a moisture absorbent containing at least a porous metal complex. The moisture-permeable sheet 3 includes a flat partition plate 3A shown in FIG. 3(A) and a spacer plate 3B shown in FIG. 3(B) which is corrugated by alternately connecting convex peaks 30 and concave valleys 31. The spacer plate 3B is formed by performing a step process such as bending on the partition plate 3A. As shown in FIG. 3(C), the bottom of the valleys 31 of the spacer plate 3B is bonded to the surface of the partition plate 3A by, for example, an adhesive to form a single-corrugated sheet 3C. Then, the peaks 30 of the spacer plate 3B of the single-corrugated sheet 3C and the surface of the partition plate 3A of another single-corrugated sheet 3C are alternately stacked in multiple layers so that the extension directions (ridge lines) of the peaks 30 of the two single-corrugated sheets 3C are perpendicular to each other, thereby forming a total heat exchange element 2 having a block-type honeycomb structure as shown in FIG. 2(A). A space 20 shown in FIG. 2(B) is a space defined by a partition plate 3A and a spacer plate 3B.
[0044] The spacing plate 3B is not limited to the moisture permeable sheet 3 processed into a corrugated step. For example, although not shown, the spacing rib can be formed of resin into any shape to form a stable ventilation passage. In this case, the resin used for the spacing rib can be polypropylene (PP), polycarbonate (PC), polystyrene (PS), acrylonitrile-butadiene-styrene (ABS), or other general resin that can be easily molded into a desired shape and can suppress deformation due to humidity.
[0045] In addition, the moisture permeable sheet 3 can be folded into various shapes other than the processing such as the spacing plate 3B. The method of forming the total heat exchange element 2 is not limited to the above-mentioned method of cross-stacking the moisture permeable sheets 3, and can be formed by various known methods as long as it has a structure in which a plurality of spaces 20 are closely arranged.
[0046] The substrate of the moisture permeable sheet 3 is not particularly limited, and for example, paper, nonwoven fabric, and plastic film can be used, but it is preferable to use a fiber substrate from the viewpoint of easy support of the porous metal complex. The fibers constituting the fiber substrate are not particularly limited, but it is preferable to include non-fibrillated fibers and fibrillated fibers. By including non-fibrillated fibers, the moisture permeable sheet 3 can easily retain the step shape by itself after step processing such as the spacing plate 3B is performed, and has excellent processability. In addition, it is possible to ensure shape stability and dimensional stability under high relative humidity or condensation atmosphere. On the other hand, by including fibrillated fibers, the moisture permeable sheet 3 can efficiently support the porous metal complex, and has excellent support of the porous metal complex. This serves to suppress the falling off of the porous metal complex under high relative humidity or condensation atmosphere. Furthermore, it is possible to reduce the amount of organic binder that is normally used to support the porous metal complex, which reduces the blockage of the pores of the porous metal complex by the organic binder, allowing the adsorption performance of the porous metal complex to be effectively exhibited.
[0047] Examples of non-fibrillated fibers include inorganic fibers such as glass fibers, ceramic fibers, and rock wool fibers; synthetic fibers such as aramid fibers, meta-aramid fibers, polybenzimidazole fibers, polyether ketone fibers, polyethylene terephthalate fibers, and nylon fibers; semi-synthetic fibers such as acetate fibers and triacetate fibers; rayon fibers; regenerated fibers such as cupra fibers; and vegetable fibers such as fibers mainly composed of cotton, hemp, and wood, and one or more of these can be used. On the other hand, examples of fibrillated fibers include pulp, in addition to the above-mentioned fibers that have been fibrillated, and one or more of these can be used.
[0048] The fibrillation method is not particularly limited, and a normal beating method can be used. A typical example is a method of fibrillation using a beating machine such as a beater or a refiner. In addition, the fibrillated fiber preferably has a Canadian Standard Freeness (CSF) of 50 ml or more and less than 800 ml when measured according to JIS P 8121-2.
[0049] The fiber diameter of the non-fibrillated fibers is not particularly limited, but is preferably 5 μm or more, and more preferably 5 μm to 30 μm. The fiber length of the non-fibrillated fibers is preferably 1 mm to 10 mm, and more preferably 2 mm to 8 mm. Since the fiber diameter of the non-fibrillated fibers is 5 μm or more and the fiber length is 1 mm or more, the strength of the moisture-permeable sheet 3 can be sufficiently ensured, so that the step shape can be easily maintained by itself after step processing such as the spacing plate 3B, and the moisture-permeable sheet 3 can be easily processed into a block-shaped total heat exchange element 2. Furthermore, since the fiber diameter of the non-fibrillated fibers is 30 μm or less and the fiber length is 10 mm or less, the moisture-permeable sheet 3 has good flexibility, and processing such as the spacing plate 3B can be easily performed, and the total heat exchange element 2 formed by the moisture-permeable sheet 3 also has flexibility. Note that fibers with different fiber diameters may be mixed.
[0050] The method of supporting the porous metal complex as the moisture absorbent on the moisture permeable sheet 3 is not particularly limited, and the porous metal complex may be adhered to the surface or inside of the moisture permeable sheet 3 using a binder or the like, an impregnation liquid containing the porous metal complex may be applied to the moisture permeable sheet 3, or the moisture permeable sheet 3 may be impregnated with the impregnation liquid. In this embodiment, the porous metal complex is supported on the moisture permeable sheet 3 using an organic binder. This can improve the flexibility and strength of the moisture permeable sheet 3, and can also suppress the porous metal complex from falling off and flowing out under high relative humidity or in a condensation atmosphere.
[0051] The organic binder is not particularly limited as long as it can adhere the porous metal complex to the moisture permeable sheet 3, and examples of the organic binder that can be used include polyvinyl alcohol-based polymers, polyacrylonitrile-based polymers, polyethylene-based polymers, polyester-based polymers, and polyphenylene ether-based polymers. Among these, it is preferable to use polyvinyl alcohol-based polymers from the viewpoint of ease of handling. The form of the organic binder is not particularly limited, but it is preferable to use a fibrous one, since the moisture permeable sheet 3 can be easily produced as described below.
[0052] The organic binder is not particularly limited, but it is preferable that the organic binder has a high melting point in water of 65° C. to 100° C., and more preferably 70° C. to 100° C. When the organic binder has a dissolution temperature in water of 65° C. or higher, the pores of the porous metal complex are prevented from being blocked by the organic binder, allowing the adsorption performance of the porous metal complex to be effectively exhibited, while when the dissolution temperature is 100° C. or lower, the porous metal complex can be supported on the moisture-permeable sheet 3 with good adhesive strength.
[0053] The water dissolution temperature of the organic binder can be measured by a known method. For example, 100 ml of pure water is placed in a beaker, heated in an oil bath with stirring until the water temperature reaches 50° C., 0.5 g of the organic binder is added thereto, the water temperature is increased at a heating rate of 2° C. / min, and the temperature at which the binder begins to dissolve and becomes translucent is measured by visual observation, thereby measuring the water dissolution temperature.
[0054] The water repellent is not particularly limited as long as it can provide water repellency while maintaining the moisture permeability of the moisture permeable sheet 3, and for example, fluorine resin, silicone resin, polyacrylic resin, polyolefin resin, etc. can be used. Among these, it is preferable to use polyacrylic resin from the viewpoint of safety and handling. In particular, the water repellent is preferably one containing a structure derived from styrene, more preferably one containing a structure having acrylic other than styrene, and may be a styrene-acrylic copolymer. This is because it is assumed that the balance between the environmental load, moisture absorption / moisture permeability, and water repellency is good. Styrene (aromatic ring), alkyl chains described in the following chemical formula, or branched and bulky alkyl chains are considered to be difficult to penetrate into the pores of the porous metal complex, and by inhibiting penetration into the pores as much as possible, the moisture absorption or moisture permeability of the porous sheet 3 can be ensured. [ka]
[0055] The styrene may not have a functional group, or may have an alkyl chain such as a methyl group at the o-, m-, or p-position. The acrylic may be an acrylic acid-based compound or a methacrylic acid with a methyl group substituted at the α-position. Styrene and acrylic may be copolymerized or may be mixed with a surfactant.
[0056] Examples of water repellents containing an alkyl chain represented by the above chemical formula, in which R1+R2 contains 5 or more carbon atoms, include butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, isopentyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, butyl 2-ethylacrylate, isobutyl 2-ethylacrylate, tert-butyl 2-ethylacrylate, pentyl 2-ethylacrylate, isopentyl 2-ethylacrylate, hexyl 2-ethylacrylate, 2-ethylhexyl 2-ethylacrylate, etc. Examples of water repellents containing an alkyl chain represented by the above chemical formula, in which R1 contains 5 or more carbon atoms, include hexyl acrylate, isohexyl acrylate, 2-ethylbutyl acrylate, heptyl acrylate, isoheptyl acrylate, 2-ethyl-pentyl acrylate, octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, etc., but are not limited thereto.
[0057] The form of the water repellent is not particularly limited, but it is preferable to use an aqueous emulsion type water repellent, since it can be applied to the moisture permeable sheet 3 safely and easily.
[0058] The content of the porous metal complex in the moisture permeable sheet 3 (i.e., the total heat exchange element 2) is not particularly limited, but is preferably 50% by mass to 80% by mass, and more preferably 55% by mass to 75% by mass. When the content of the porous metal complex is 50% by mass or more, the moisture permeable sheet 3 can exhibit excellent moisture exchange performance due to the large amount of porous metal complex, while when the content is 80% by mass or less, the porous metal complex can be supported on the adsorption sheet 3 without any problems, so that the porous metal complex can be prevented from falling off from the moisture permeable sheet 3 and the decrease in strength of the moisture permeable sheet 3 can also be prevented.
[0059] The total content of non-fibrillated fibers and fibrillated fibers in the moisture permeable sheet 3 (i.e., the total heat exchange element 2) is not particularly limited, but is preferably 5% by mass to 25% by mass, and more preferably 10% by mass to 25% by mass. When the fiber content is 5% by mass or more, the moisture permeable sheet 3 can favorably support the porous metal complex, so that the porous metal complex can be prevented from falling off from the moisture permeable sheet 3 and a decrease in the strength of the moisture permeable sheet 3 can also be prevented. On the other hand, when the fiber content is 25% by mass or less, the moisture permeable sheet 3 can contain a larger amount of the porous metal complex, so that the large amount of the porous metal complex can provide excellent humidity exchange performance.
[0060] The content of the organic binder in the moisture permeable sheet 3 (i.e., the total heat exchange element 2) is preferably 3% by mass to 15% by mass, and more preferably 4% by mass to 12% by mass. When the content of the organic binder is 3% by mass or more, the moisture permeable sheet 3 can improve the support of the porous metal complex and the flexibility of the moisture permeable sheet 3, while when the content is 15% by mass or less, the pores of the porous metal complex can be prevented from being blocked by the organic binder, which reduces the adsorption performance of the porous metal complex, so that the moisture permeable sheet 3 can exhibit excellent moisture exchange performance.
[0061] In this way, even if the moisture permeable sheet 3 (i.e., the total heat exchange element 2) contains a small amount of organic binder, the fibrillated fibers fully support the porous metal complex, and the high moisture adsorption rate of the porous metal complex gives the moisture permeable sheet 3 sufficient flexibility. As a result, the high adsorption performance of the porous metal complex is not inhibited by the organic binder, and the moisture permeable sheet 3 can exhibit excellent humidity exchange performance due to the high adsorption performance of the porous metal complex. Furthermore, sufficient shape stability and dimensional stability are provided in a high relative humidity atmosphere, and the porous metal complex can be prevented from falling off or flowing out.
[0062] Furthermore, the content of the water repellent in the moisture permeable sheet 3 (i.e., the total heat exchange element 2) is not particularly limited, but is preferably 2% by mass to 10% by mass, and more preferably 4% by mass to 8% by mass. When the content of the water repellent is 2% by mass or more, the moisture permeable sheet 3 can exhibit sufficient water repellency, while when the content is 10% by mass or less, the moisture permeable sheet 3 can maintain sufficient moisture permeability.
[0063] The thickness of the moisture permeable sheet 3 is not particularly limited, but is preferably 0.1 mm to 0.9 mm, and more preferably 0.1 mm to 0.7 mm. When the thickness of the moisture permeable sheet 3 is 0.1 mm or more, the strength of the moisture permeable sheet 3 can be sufficiently ensured, so that the moisture permeable sheet 3 can be easily processed into a block-shaped total heat exchange element 2, while when the thickness is 0.9 mm or less, the pressure loss when air passes through the inside of the total heat exchange element 2 processed into a block shape can be suppressed.
[0064] The basis weight of the moisture permeable sheet 3 is not particularly limited, but is preferably 25 g / m 2 ~200g / m 2 It is preferable that the thickness is 40 g / m 2 ~150g / m 2 It is more preferable that the basis weight of the moisture permeable sheet 3 is 25 g / m 2 By setting the above value, the strength of the moisture permeable sheet 3 can be sufficiently ensured, so that the moisture permeable sheet 3 can be easily processed into a block-shaped total heat exchange element 2. On the other hand, the basis weight is preferably 200 g / m 2 By satisfying the condition below, it is possible to suppress pressure loss when air passes through the inside of the total heat exchange element 2 processed into a block shape.
[0065] The specific tensile elongation, which is an index of flexibility of the moisture-permeable sheet 3, is not particularly limited, but is preferably 5%·m / g or more. When the specific tensile elongation of the moisture-permeable sheet 3 is 5%·m / g or more, it is possible to suppress the occurrence of cracks and the like in the moisture-permeable sheet 3 when the moisture-permeable sheet 3 is processed to form the total heat exchange element 2, for example by processing the spacer 3B.
[0066] The tensile elongation ratio of the moisture permeable sheet 3 can be determined, for example, as follows. A 15 mm x 100 mm test piece cut out from a moisture permeable sheet sample is dried at 120°C for 1 hour and its weight is measured. The dried sample is then left to stand for 1 hour in an atmosphere of 22°C and 40% RH, and the maximum point elongation [%] is measured using a tensile / compression tester (TENSILON RTG-1310, manufactured by A&D). The chuck distance is 50 mm and the tensile speed is 15 mm / min. The tensile elongation ratio can be determined from the obtained data using the following formula 2.
[0067] Specific tensile elongation [% m / g] = maximum point elongation [%] / sample width [m] / moisture permeable sheet basis weight [g / m2] (Equation 2)
[0068] The method for producing the moisture-permeable sheet 3 is not particularly limited, and a conventionally known method can be used. Among them, a wet sheeting method can be mentioned, in which the porous metal complex, fiber, and organic binder described above are dispersed in water or an organic solvent (or a mixture thereof), and then formed, dehydrated, and dried to form a sheet. After the sheeting process, it is preferable to carry out a desolvation process for removing the solvent contained in the moisture-permeable sheet 3. In addition, in the sheeting process, it is preferable that the porous metal complex is mixed with the organic binder described above in a state in which the solvent molecules are adsorbed in the pores. If the porous metal complex has solvent molecules in the pores, there is no risk of the organic binder blocking the pores in the sheeting process, and the high adsorption performance of the porous metal complex can be ensured by removing the solvent molecules from the pores by a desolvation process after the sheeting process. Usually, the porous metal complex has solvent molecules adsorbed in the pores at the stage of synthesis, but when the solvent molecules are not adsorbed in the pores or the amount of adsorption of the solvent molecules is insufficient, it is preferable to adsorb an organic solvent in the pores. Here, the solvent refers to water or a general organic solvent.
[0069] The method of incorporating a water repellent into the moisture-permeable sheet 3 is not particularly limited, and a conventionally known method can be used. For example, a method of impregnating the moisture-permeable sheet 3 before water repellent processing with an aqueous emulsion of the water repellent binder using a water repellent binder as the water repellent, or a method of spraying and coating the aqueous emulsion of the water repellent binder can be mentioned. After the water repellent binder coating, it is preferable to carry out a solvent removal process to remove the solvent contained in the moisture-permeable sheet 3. In addition, in the water repellent binder coating, it is preferable that the porous metal complex in the moisture-permeable sheet 3 is mixed with the above-mentioned water repellent binder in a state in which the solvent molecules are adsorbed in the pores. If the porous metal complex has solvent molecules in the pores, there is no risk of the water repellent binder blocking the pores in the water repellent binder coating, and the high adsorption performance of the porous metal complex can be ensured by removing the solvent molecules from the pores by a solvent removal process after the water repellent binder coating. In general, when a porous metal complex is synthesized, solvent molecules are adsorbed in the pores, but when the solvent molecules are not adsorbed in the pores or the amount of the solvent molecules adsorbed is insufficient, it is preferable to adsorb an organic solvent in the pores. Here, the solvent refers to water or a general organic solvent.
[0070] As a method for incorporating a water repellent agent in the moisture permeable sheet 3, for example, the base material of the moisture permeable sheet 3 may be subjected to a surface treatment to impart water repellency as necessary. The moisture permeable sheet 3 may also be incorporated with a water repellent agent by a method other than those described above.
[0071] As a condition for the solvent removal treatment, the temperature is not particularly limited, but is preferably 50°C to 300°C, and more preferably 80°C to 200°C. By setting the temperature at 50°C or higher, the solvent can be removed without any problems, and the high adsorption performance of the porous metal complex can be ensured. On the other hand, by setting the temperature at 300°C or lower, the pore structure of the porous metal complex can be prevented from being destroyed, and the high adsorption performance of the porous metal complex can be ensured. In addition, the solvent can be removed more efficiently by performing the solvent removal treatment under reduced pressure. The pressure is not particularly limited and may be appropriately adjusted depending on the physical properties and amount of the porous metal complex. For example, a pressure of 10-3 Pa~10 -5 Pa is an example, and more preferably 10 -1 Pa~10 -5 Examples of the solvent removal treatment time include, but are not limited to, 1 hour to 100 hours, more preferably 3 hours to 48 hours, and further preferably 3 hours to 24 hours. The most preferable conditions for the solvent removal treatment are, for example, a temperature of 80°C to 200°C under vacuum conditions and a treatment time of 3 hours to 24 hours.
[0072] Returning to Fig. 1, the total heat exchange element 2 is stored at a predetermined position in the housing 4 so that the stacking direction is perpendicular to the ventilation direction, and is supported and fixed by a frame 40. To prevent the air flows of outside air (OA), return air (RA), supply air (SA), and exhaust air (EA) with different temperatures and / or humidity from mixing, the passage spaces of each air flow are separated by partitions 41. Each air flow may be generated by natural ventilation driven by the pressure difference between the inside and outside of the room, or may be generated by forced ventilation in which a driving force for air circulation is provided by a ventilation fan (not shown) or the like.
[0073] As described above, the total heat exchange element 2 is configured such that the open layers 21, 23 through which the air flow can pass and the closed layers 22, 24 through which the air flow cannot pass are alternately stacked, and the two air flows pass perpendicular to the stacking direction without mixing. Outside air (OA), which is the first air flow, flows into the first air supply port 50 and flows through the open layer 21, and return air (RA), which is the second air flow, flows into the second air supply port 51 and flows through the open layer 23. As a result, the first air flow and the second air flow do not mix with each other due to the partition plate 3A, and after exchanging sensible heat and latent heat, the supply air (SA), which is the first air flow, is discharged from the first exhaust port 60, and the exhaust air (EA), which is the second air flow, is discharged from the second exhaust port 61. The total heat exchange element 2 can continuously perform the above heat exchange without requiring a driving source. Furthermore, the moisture permeable sheet 3 described above can be used sufficiently even in a high relative humidity environment or in a condensation atmosphere due to its water resistance and water repellency.
[0074] Next, referring to FIG. 1, the heat exchange operation of the total heat exchanger 1 of this embodiment will be described. The outside air (OA) to be treated is taken into the first air inlet 50 by the pressure difference between the inside and outside of the room or a fan (not shown) or the like, and is supplied to the opening 21 of the total heat exchange element 2. Meanwhile, the return air (RA) to be treated is taken into the second air inlet 51 by the pressure difference between the inside and outside of the room or a fan (not shown) or the like, and is supplied to the opening 23 of the total heat exchange element 2. The two airs (OA, RA) with different temperatures and / or humidities exchange sensible heat and latent heat without direct contact with each other due to the partition plate 3A, and the outside air (OA) recovers the temperature and humidity of the return air (RA) to become the supply air (SA), while the return air (RA) from which the temperature and humidity have been recovered becomes the exhaust air (EA) and is discharged to the outside of the system. The purpose is to save energy in air conditioning by bringing the outside air (OA) from the outside of the room closer to the temperature and humidity conditions of the return air (RA) from the inside of the room.
[0075] According to the total heat exchanger 1 of the present embodiment having the above-mentioned configuration, a porous metal complex having a saturated moisture adsorption rate difference of 20% or more by mass between 25°C, relative pressure 0.6 and 25°C, relative pressure 0.3, and a water repellent are used as the moisture absorbent, and since the moisture permeability of the moisture permeable sheet 3 containing 50% or more by mass of the porous metal complex is high, a high humidity exchange rate (recovery of latent heat) can be achieved, and since the water resistance and water repellency of the moisture permeable sheet 3 containing 2% or more by mass of the water repellent are high, it can be stably operated even in a high relative humidity atmosphere or a condensation atmosphere, and can be easily washed with water. Therefore, the total heat exchanger 1 of the present embodiment can provide an air conditioning system that is energy-saving, durable, and easy to maintain.
[0076] In addition, total heat exchange elements carrying inorganic salts have the problem of carryover due to deliquescence of inorganic salts when used in a high relative humidity atmosphere. Total heat exchange elements containing inorganic adsorbents are poor in flexibility and have difficulty in long-term use durability due to cracking or powdering. Total heat exchange elements containing organic polymer adsorbents have the problem of large dimensional changes in a high humidity atmosphere and poor stability as an element. However, since the porous metal complex is not deliquescent, and the moisture permeable sheet 3 has both flexibility and strength and is excellent in shape stability and dimensional stability in a high relative humidity atmosphere, the above problems can be suppressed even if the total heat exchanger 1 is used continuously.
[0077] Although the embodiment of the present invention has been described above, the above-mentioned embodiment is illustrative and not restrictive, and therefore the present invention is not limited to the above-mentioned embodiment. The technical scope of the present invention is defined by the claims, and includes all modifications within the meaning and scope equivalent to the description of the claims, and therefore the present invention can be modified in various ways without departing from the spirit of the present invention.
[0078] For example, in the embodiment described above using Figure 1, a filter for preventing contamination of the total heat exchange element 2 is not installed, and a blower fan (not shown) is not stored inside the housing 4. However, as in the total heat exchanger 1A of a modified example of this embodiment shown in Figure 4, a filter 7 for preventing contamination of the total heat exchange element 2 may be installed, and a blower fan 8 may be stored inside the housing 4.
[0079] In addition, in the above-mentioned embodiment, the total heat exchanger 1, 1A is a stationary device having no driving section, and is equipped with a total heat exchange element 2 formed into a block shape by alternatingly stacking single-stage sheets 3C consisting of partition plates 3A and spacing plates, and the single-stage sheet 3C uses a moisture-permeable sheet 3 containing a porous metal complex composed of metal ions and organic ligands, in which the difference in saturated moisture adsorption rate between 25°C and a relative pressure of 0.6 and 25°C and a relative pressure of 0.3 is 20 mass% or more.
[0080] However, the total heat exchanger of the present invention is not limited to the above, and for example, as in another embodiment shown in Fig. 5, the moisture-permeable sheet 3 containing the porous metal complex described above can be processed into a rotary total heat exchange element 2B, which can be rotated in a circumferential direction to form a rotary total heat exchanger 1B that continuously exchanges total heat between the outside air (OA) and the inside air (RA). The rotary total heat exchange element 2B is supported by a housing 4B shown in Fig. 5 with the rotation axis oriented horizontally, and is divided into an outside air (OA) circulation zone and an inside air (RA) circulation zone, and is driven to rotate in a circumferential direction around the rotation axis by a drive motor 90 and a drive belt 91. In large buildings such as factories and commercial facilities, rotary total heat exchangers are often preferably used from the viewpoint of processing capacity.
[0081] Moreover, the total heat exchanger 1 (or 1A) of the above-mentioned embodiment can be combined with another air conditioning system to provide an air conditioning system with additional functions or energy savings. For example, as in the embodiment shown in Fig. 6, the total heat exchanger 1 (or 1A) described above can be combined with a heat pump. This is an air conditioning system in which the evaporator of the heat pump is used as an intake air cooler 100 after the outside air (OA) is totally heat exchanged with the inside air (RA).
[0082] As in the embodiment shown in Fig. 7, the total heat exchanger 1 (or 1A) of the above-mentioned embodiment can be combined with a desiccant air conditioner 140. According to this system, outside air (OA) is subjected to total heat exchange by the front-stage total heat exchanger 1 (or 1A), passes through a cooler 100, and becomes supply air (SA) after being dehumidified by the rear-stage desiccant air conditioner 140. After being heated by a heater 110, inside air (RA) is humidified by the desiccant air conditioner 140, and then undergoes total heat exchange by the total heat exchanger 1 (or 1A) to become exhaust air (EA).
[0083] As in the embodiment shown in Fig. 8, the total heat exchanger 1 (or 1A) of the above-mentioned embodiment can be combined with a desiccant air conditioner 140 and a heat pump. According to this system, the evaporator and condenser of the heat pump in the embodiment of Fig. 7 are used as the cooler 100 and heater 110, respectively. Since the exhaust heat of the heat pump can be utilized, this system can be operated in a more energy-efficient manner. EXAMPLES
[0084] The present invention will be described in more detail below with reference to examples thereof, but the present invention is not limited to the following examples.
[0085] <Example 1> A porous metal complex was synthesized by dissolving 16.2 g (40 mmol) of Fe(NO3)3·9H2O and 7.5 g (36 mmol) of trimesic acid in 32 ml of water and heating at 95°C for 15 hours. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. The BET specific surface area was 1,575 m 2 The difference in saturated water adsorption rate between the case where the sample was 1 / g at 25° C. and a relative pressure of 0.6 and the case where the sample was 1 / g at 25° C. and a relative pressure of 0.3 was 28 mass %.
[0086] The porous metal complex thus synthesized was then immersed in water for 24 hours and then filtered to obtain a porous metal complex sample in which solvent molecules were adsorbed in the pores. This porous metal complex sample was mixed in a ratio of 66 mass% (excluding solvent molecules), 13.6 mass% of aramid fiber as a non-fibrillated fiber, 8.5 mass% of aramid fiber as a fibrillated fiber, and 11.9 mass% of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder, to produce a porous metal complex sample with a basis weight of 60 g / m. 2 A moisture-permeable sheet sample was obtained using a wet papermaking machine (manufactured by Toyobo Engineering Co., Ltd., the same applies below) with a mass of 130° C. and then subjected to a solvent removal treatment for 24 hours under vacuum conditions to obtain a moisture-permeable sheet.
[0087] The moisture-permeable sheet thus prepared was then subjected to moisture conditioning treatment for 24 hours at 20°C in a water vapor atmosphere at a relative pressure of 0.95, and an acrylic styrene-based water-repellent binder A adjusted to a solid content concentration of 5% by mass as a water repellent agent was spray-coated to obtain a moisture-permeable sheet sample. Further, the solvent was removed at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0088] <Example 2> The moisture-permeable sheet before the water-repellent binder coating obtained in the same manner as in Example 1 was subjected to moisture conditioning treatment at 20°C under a water vapor atmosphere of a relative pressure of 0.95 for 24 hours, and impregnated with an acrylic styrene-based water-repellent binder A adjusted to a solid content concentration of 5 mass% as a water repellent agent to obtain a moisture-permeable sheet sample. Further, a solvent removal treatment was performed at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0089] <Example 3> The moisture-permeable sheet before the water-repellent binder coating obtained in the same manner as in Example 1 was subjected to moisture conditioning treatment at 20°C under a water vapor atmosphere at a relative pressure of 0.95 for 24 hours, and an acrylic styrene-based water-repellent binder B adjusted to a solid content concentration of 5% by mass as a water repellent was spray-coated to obtain a moisture-permeable sheet sample. Further, a solvent removal treatment was performed at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0090] <Example 4> The moisture-permeable sheet before the water-repellent binder coating obtained in the same manner as in Example 1 was subjected to moisture conditioning treatment at 20°C under a water vapor atmosphere of a relative pressure of 0.95 for 24 hours, and impregnated with an acrylic styrene-based water-repellent binder B adjusted to a solid content concentration of 5 mass% as a water repellent agent to obtain a moisture-permeable sheet sample. Further, a solvent removal treatment was performed at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0091] <Example 5> The moisture-permeable sheet before the water-repellent binder coating obtained in the same manner as in Example 1 was subjected to moisture conditioning treatment at 20°C under a water vapor atmosphere of a relative pressure of 0.95 for 24 hours, and an acrylic styrene-based water-repellent binder C adjusted to a solid content concentration of 5% by mass as a water repellent agent was spray-coated to obtain a moisture-permeable sheet sample. Further, a solvent removal treatment was performed at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0092] <Example 6> The moisture-permeable sheet before the water-repellent binder coating obtained in the same manner as in Example 1 was subjected to moisture conditioning treatment at 20°C under a water vapor atmosphere of a relative pressure of 0.95 for 24 hours, and impregnated with an acrylic styrene-based water-repellent binder C adjusted to a solid content concentration of 5 mass% as a water repellent agent to obtain a moisture-permeable sheet sample. Further, a solvent removal treatment was performed at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0093] <Example 7> 5.3 g (22.7 mmol) of zirconium chloride and 4.5 g (22.8 mmol) of 2,5-dihydroxy-terephthalic acid were dissolved in 500 ml of N,N-dimethylformaldehyde and heated at 120 °C for 24 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement, and the BET specific surface area was found to be 1,145 m. 2 The difference in saturated water adsorption rate between the case where the sample was 1 / g at 25° C. and a relative pressure of 0.6 and the case where the sample was 1 / g at 25° C. and a relative pressure of 0.3 was 27 mass %.
[0094] The porous metal complex synthesized above was then immersed in water for 24 hours and then filtered to obtain a porous metal complex sample with solvent molecules adsorbed in the pores. This porous metal complex sample was mixed in a ratio of 70 mass% (excluding solvent molecules), 12 mass% of aramid fiber as a non-fibrillated fiber, 7.5 mass% of aramid fiber as a fibrillated fiber, and 10.5 mass% of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder, and the resulting mixture had a basis weight of 60 g / m 2 A moisture-permeable sheet sample was prepared using a wet papermaking device with a mass of 130°C. The solvent was removed at 130°C under vacuum for 24 hours to obtain a moisture-permeable sheet.
[0095] The moisture-permeable sheet thus prepared was then subjected to moisture conditioning treatment for 24 hours at 20°C in a water vapor atmosphere at a relative pressure of 0.95, and impregnated with an acrylic styrene-based water-repellent binder A adjusted to a solid content concentration of 5% by mass as a water repellent agent to obtain a moisture-permeable sheet sample. Further, the sheet was subjected to a solvent removal treatment for 24 hours at 130°C under vacuum conditions to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0096] <Example 8> 5.3 g (22.7 mmol) of zirconium chloride and 3.78 g (22.8 mmol) of terephthalic acid were dissolved in 500 ml of N,N-dimethylformaldehyde and heated at 120°C for 24 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement, and the BET specific surface area was found to be 1,283 m. 2 The difference in saturated water adsorption rate between the case where the sample was 25° C. / g and a relative pressure of 0.6 and the case where the sample was 25° C. and a relative pressure of 0.3 was 33 mass %.
[0097] The porous metal complex thus synthesized was then immersed in water for 24 hours and then filtered to obtain a porous metal complex sample in which solvent molecules were adsorbed in the pores. This porous metal complex sample was mixed in a ratio of 60 mass% (excluding solvent molecules), 16 mass% aramid fiber as a non-fibrillated fiber, 10 mass% aramid fiber as a fibrillated fiber, and 14 mass% polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder, to obtain a porous metal complex sample having a basis weight of 60 g / m. 2 A moisture-permeable sheet sample was prepared using a wet papermaking device with a mass of 130°C. The solvent was removed at 130°C under vacuum for 24 hours to obtain a moisture-permeable sheet.
[0098] The moisture-permeable sheet thus prepared was then subjected to moisture conditioning treatment for 24 hours at 20°C in a water vapor atmosphere at a relative pressure of 0.95, and impregnated with an acrylic styrene-based water-repellent binder A adjusted to a solid content concentration of 5% by mass as a water repellent agent to obtain a moisture-permeable sheet sample. Further, the sheet was subjected to a solvent removal treatment for 24 hours at 130°C under vacuum conditions to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0099] <Comparative Example 1> The moisture-permeable sheet obtained in the same manner as in Example 1 before being coated with the water-repellent binder was used as it was to measure / evaluate the moisture absorption rate, moisture permeability, water resistance, and water repellency.
[0100] <Comparative Example 2> The moisture-permeable sheet before the water-repellent binder coating obtained in the same manner as in Example 1 was subjected to moisture conditioning treatment at 20°C under a water vapor atmosphere at a relative pressure of 0.95 for 24 hours, and a polyurethane-based water-repellent binder D adjusted to a solid content concentration of 5 mass% as a water repellent was spray-coated to obtain a moisture-permeable sheet sample. Further, a solvent removal treatment was performed at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0101] <Comparative Example 3> The moisture-permeable sheet before the water-repellent binder coating obtained in the same manner as in Example 1 was subjected to moisture conditioning treatment at 20°C in a water vapor atmosphere at a relative pressure of 0.95 for 24 hours, and impregnated with a polyurethane-based water-repellent binder D adjusted to a solid content concentration of 5 mass% as a water repellent agent to obtain a moisture-permeable sheet sample. Further, a solvent removal treatment was performed at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0102] <Comparative Example 4> A porous metal complex was synthesized by dissolving 200 g (0.62 mol) of ZrOCl2·8H2O and 72 g (0.62 mol) of fumaric acid in 2 L of N,N-dimethylformaldehyde and 700 mL of formic acid, and heating at 130 °C for 6 hours. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement, and the BET specific surface area was found to be 884 m 2 The difference in saturated water adsorption rate between the case where the sample was 1 / g at 25° C. and a relative pressure of 0.6 and the case where the sample was 1 / g at 25° C. and a relative pressure of 0.3 was 7 mass %.
[0103] The porous metal complex thus synthesized was then immersed in water for 24 hours and then filtered to obtain a porous metal complex sample in which solvent molecules were adsorbed in the pores. This porous metal complex sample was mixed in a ratio of 75 mass% (excluding solvent molecules), 10 mass% aramid fiber as a non-fibrillated fiber, 6.25 mass% aramid fiber as a fibrillated fiber, and 8.75 mass% polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder, to obtain a porous metal complex sample having a basis weight of 60 g / m. 2 A moisture-permeable sheet sample was prepared using a wet papermaking device with a mass of 130°C. The solvent was removed at 130°C under vacuum for 24 hours to obtain a moisture-permeable sheet.
[0104] The moisture-permeable sheet thus prepared was then subjected to moisture conditioning treatment for 24 hours at 20°C in a water vapor atmosphere at a relative pressure of 0.95, and impregnated with an acrylic styrene-based water-repellent binder A adjusted to a solid content concentration of 5% by mass as a water repellent agent to obtain a moisture-permeable sheet sample. Further, the sheet was subjected to a solvent removal treatment for 24 hours at 130°C under vacuum conditions to obtain a moisture-permeable sheet. The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured / evaluated.
[0105] <Comparative Example 5> The porous metal complex sample obtained in the same manner as in Example 1 was mixed in a ratio of 90 mass% (excluding solvent molecules), 4 mass% of aramid fiber as a non-fibrillated fiber, 2.5 mass% of aramid fiber as a non-fibrillated fiber, and 3.5 mass% of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70°C (catalog value) as an organic binder, to obtain a 60 g / m2 porous metal complex sample. 2 A moisture permeable sheet sample was prepared using a wet papermaking device with a mass of 1.0 kg / m2. The solvent was removed at 130°C under vacuum for 24 hours to obtain moisture permeable sheet 3. The obtained moisture permeable sheet 3 was very brittle and had poor shape stability, making it impossible to perform various measurements.
[0106] <Reference example 1> Basis weight 25g / m 2 The glass fiber paper was dip-coated in an aqueous dispersion containing 20% by mass of a polymeric moisture absorbent based on polyacrylate, and dried at 130°C under vacuum conditions for 24 hours to obtain a moisture-permeable sheet. The basis weight of the obtained moisture-permeable sheet was 60 g / m 2 The moisture absorption rate, moisture permeability, water resistance, and water repellency of the obtained moisture-permeable sheet were measured.
[0107] [Measurement and Evaluation] Each of the moisture permeable sheets prepared in the above Examples and Comparative Examples was measured and evaluated for the following items. [Moisture permeability] The moisture permeability is JIS Z 0208, and is measured under conditions of 20°C and 65% RH, with a moisture permeability area of 28.3 cm 2 The measurements were carried out as moisture permeability (g / (m2 When the moisture permeable sheet is used as a partition plate for a total heat exchanger, the moisture permeability at 20℃ × 65% RH is 800 (g / (m 2 24hr)) or more, preferably 1,200 (g / (m 2 24hr)) or more, and more preferably 1,500 (g / (m 2 24 hours or more is preferable.
[0108] [Difference in saturated water adsorption rate] The saturated water adsorption rate of a porous metal complex (moisture absorbent) at 25°C and a relative pressure of 0.6 was measured by taking about 100 mg of the porous metal complex (before treatment with water or organic solvent), vacuum drying it at 120°C for 12 hours, weighing it, and then using a high-precision gas / vapor adsorption measurement device (BELSORP-max, manufactured by BEL Japan) to measure the amount of water vapor adsorption at 25°C at 40 points while gradually increasing the relative pressure in the range of 0.02 to 0.95, and creating an adsorption isotherm. At this time, the target relative pressure was set to 0.001, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9, and the allowable increase / decrease in the amount of adsorption was set to 30 cm at a relative pressure of 0 to 0.3. 2 / g, 50 cm at relative pressures of 0.3 to 0.5 2 / g, 30 cm at relative pressures of 0.5 and above 2 / g, and an adsorption isotherm is created. Then, the saturated water adsorption rate [%] is calculated from the amount of water adsorbed [g] per 1 g of the porous metal complex at a relative pressure of 0.6 using the following formula 1.
[0109] Saturated water adsorption rate [%] = Water adsorption amount [g] per 1 g of porous metal complex × 100 (Equation 1)
[0110] Similarly, the saturated water adsorption rate of the porous metal complex at 25° C. and a relative pressure of 0.3 is calculated from the water adsorption amount [g] per 1 g of the porous metal complex at a relative pressure of 0.3 using the above formula 1 after creating the above adsorption isotherm. The difference in saturated water adsorption rate is determined by subtracting the saturated water adsorption rate of the porous metal complex at 25° C. and a relative pressure of 0.3 from the saturated water adsorption rate of the porous metal complex at 25° C. and a relative pressure of 0.6.
[0111] [Saturated water adsorption rate] The saturated moisture adsorption rate of each moisture permeable sheet is determined by weighing out approximately 0.2 g of the sample, drying it overnight in a vacuum dryer at 130°C, and measuring the dry weight (Wd(g)). Next, the sample is left for 24 hours in a thermo-hygrostat adjusted to a temperature of 20°C and a relative humidity of 65%RH, and the weight of the moisture-absorbed sample is measured (Ww(g)). Based on the above values, the weight is calculated using the following formula 3. Saturated moisture absorption rate (weight %) = {(Ww-Wd) / Wd}×100 (Formula 3)
[0112] [water resistance] The water resistance of each moisture permeable sheet is measured by weighing out about 0.2 g of a sample, immersing it in water for 5 seconds, and then vacuum drying it at 130°C overnight. The moisture absorption rate after this is expressed as a percentage compared to the moisture absorption rate of the sample before immersion in water, which was measured in advance. Evaluations are 99% or more as ◯ (good), and less than 99% as × (unacceptable). Here, a test is conducted to show that water resistance does not decrease even after immersion in water.
[0113] [Water repellency] The water repellency of each moisture permeable sheet is evaluated by cutting a sample into a size of 3 cm x 3 cm, using an automatic contact angle meter (DM-501, manufactured by Kyowa Interface Science Co., Ltd.) to record the change in contact angle over time at 0.5 second intervals, and using the value calculated by linear approximation of the rate of change in contact angle per unit time. Evaluation is as follows: less than 0.5° / sec is ◯ (good), 0.5° / sec or more is × (bad).
[0114] [Dissolution temperature in water] The water dissolution temperature of the organic binders used in the examples and comparative examples is measured by the following measurement method. Put 4 mL of pure water and 0.02 g of organic binder into a 6 mL glass bottle. Place the glass bottle in a water bath heated in 5°C increments from 50°C for 10 minutes. Stir the organic binder in the bottle with a spatula every 2 minutes, and measure the temperature when the binder begins to dissolve and becomes translucent. The actual measurement results were the same as the catalog value.
[0115] [Total heat exchange element] Using each of the moisture-permeable sheets prepared in the above Examples and Comparative Examples, total heat exchange elements were prepared in the following manner. The single-stage processing was carried out using a single facer. The moisture permeable sheet was divided into a spacer (core) and a partition (liner), and an adhesive was applied to the top of the core, which was stepped using a corrugation roll. The core was then heat-pressed to the liner using a press roll to perform single-stage processing, resulting in a corrugation height of 1.2 mm, a corrugation pitch of 2.4 mm, and a surface area of 4,000 m. 2 / m 3 A single-corrugated sheet of Example 1 was obtained using the moisture-permeable sheet of Example 1. Similarly, a single-corrugated sheet of Examples 2 to 8 and Comparative Examples 1 to 4 was obtained using the moisture-permeable sheets of Examples 2 to 8 and Comparative Examples 1 to 4, respectively.
[0116] The single-corrugated sheets were laminated so that the corrugation directions crossed each other to produce a total heat exchange element of 700 mm in length, 700 mm in width, and 1,260 mm in height. The total heat exchange element of Example 1 was obtained from the single-corrugated sheet of Example 1. Similarly, the total heat exchange elements of Examples 2 to 8 and Comparative Examples 1 to 4 were obtained from the single-corrugated sheets of Examples 2 to 8 and Comparative Examples 1 to 4, respectively.
[0117] The total heat exchange elements of each of the examples and comparative examples obtained above were installed in a total heat exchanger 1 shown in FIG. 1. Air (OA) with a temperature of 0° C. and an absolute humidity of 1.9 g / kg [DA] was introduced into the device at a flow rate of 40 m as the treatment air assumed to be used in winter. 3 The supply air (SA) after total heat exchange that passed through the opening 21 was supplied to the room. In addition, air (RA) with a temperature of 20°C and an absolute humidity of 7.3 g / kg [DA] was introduced into the room at a flow rate of 41 m 3 / h into the opening 23. The humidity exchange efficiency was evaluated by calculating the humidity exchange efficiency from the obtained data of each absolute humidity using the following formula 4. Humidity exchange efficiency of less than 70% was indicated as × (unacceptable) and 70% or more was indicated as ◯ (good).
[0118] Humidity exchange efficiency (%) = {absolute humidity of supply air (SA) [g / kg [DA]] - absolute humidity of outside air (OA) [g / kg [DA]]} / {absolute humidity of return air (RA) [g / kg [DA]] - absolute humidity of outside air (OA) [g / kg [DA]]} x 100 (Equation 4)
[0119] Table 1 shows the results of the above measurements and evaluations. [Table 1]
[0120] As shown in Table 1, in Examples 1 to 8, the water resistance, water repellency, and humidity exchange efficiency were all evaluated as ◯, whereas in Comparative Examples 1 to 4 and Reference Example 1, any one of the water resistance, water repellency, and humidity exchange efficiency was evaluated as ×. [Industrial Applicability]
[0121] The moisture-permeable sheet of the present invention has high moisture permeability and excellent water resistance and water repellency, and the total heat exchange element and total heat exchanger of the present invention using the moisture-permeable sheet have excellent moisture permeability, can operate stably even in a high relative humidity region or in a condensation environment, and can be easily washed with water. Therefore, it is expected to make a great contribution to the industrial world. [Explanation of symbols]
[0122] 1,1A,1B...Total heat exchanger 2, 2B: Total heat exchange element 3. Breathable sheet 3A··Partition plate 3B... Spacing plate 3C··Single-tiered sheet 4. Housing 7. Filter 8. Blower fan 20...space 21 Opening 22. Non-opening 23 Opening 24. Non-opening 30. Yamabe 31 Valley 40 Frame 41...bulkhead 50··First air intake 51 Second air intake 60··First exhaust port 61 Second exhaust port 90··Drive motor 91 Drive belt 100·· Cooler (evaporator in case of heat pump) 110··Heater (condenser in case of heat pump) 120··Compressor 130 Expansion valve 140··Desiccant air conditioner
Claims
1. A porous metal complex having a metal ion and an organic ligand; Water repellent and A fiber base material; A moisture-permeable sheet comprising: The porous metal complex is one or two kinds of porous metal complexes selected from the group consisting of a porous metal complex in which the metal ion is iron and the organic ligand is trimesic acid, and a porous metal complex in which the metal ion is zirconium chloride and the organic ligand is terephthalic acid; The content of the porous metal complex in the moisture permeable sheet is 55% by mass or more and 64% by mass or less, A moisture-permeable sheet, characterized in that the content of the water repellent in the moisture-permeable sheet is 4 mass % or more and 11 mass % or less.
2. 2. The moisture permeable sheet according to claim 1, comprising non-fibrillated fibers and fibrillated fibers.
3. A moisture-permeable sheet as described in claim 1 or 2, further characterized in containing an organic binder having a water dissolution temperature of 65°C to 100°C.
4. 4. The moisture permeable sheet according to claim 1, wherein the water repellent is a copolymer and / or a mixture of styrene and acrylic.
5. A total heat exchange element comprising the moisture permeable sheet according to any one of claims 1 to 4 as a partition plate, through which two air flows having different temperatures and / or humidities are circulated, and through which sensible heat and / or latent heat of the two air flows are exchanged.
6. A total heat exchanger comprising: the total heat exchange element according to claim 5; and a housing for housing the total heat exchange element.
7. An air conditioning system comprising the total heat exchanger according to claim 6 and a heat pump.
8. An air conditioning system comprising the total heat exchanger according to claim 6 and a desiccant air conditioner.
Citation Information
Patent Citations
Total enthalpy heat exchanger
JP2008089199A
Total enthalpy heat exchange element and total enthalpy heat exchanger
JP2011163651A
Adsorption sheet and adsorption element using the same
JP2013154301A
Outside air treatment machine and outside air treatment method using desiccant rotor
JP2019066155A
Molded body containing porous metal complex, and manufacturing method and device for adsorption and desorption thereof
JP2019162574A